HOW TO ASSESS THE PROFESSIONAL COMPETENCE - Marina Yu. Prakhova; Nadezhda V. Zaichenko; Andrey N. Krasnov (Высшее образование в России, 2016)
Implementation of the competency approach in modern state educational standards radically changed an approach to the solution of many issues, including the issue of education outcomes evaluation. The problems of transition from assessing knowledge and skills to the evaluation of competencies are considered. Several variants of this assessment are suggested.